Serum glutathione peroxidase-3 concentration at diagnosis as a biomarker for assessing disease activity and damage of antineutrophil cytoplasmic antibody-associated vasculitis at diagnosis - Chung, Jihye; Ha, Jang Woo; Park, Yong-Beom; Lee, Sang-Won (Frontiers in Molecular Biosciences, 2025)
BackgroundIn this study, we investigated whether serum glutathione peroxidase-1 (GPX-3) concentration at diagnosis could be used to assess vasculitis activity and damage at diagnosis in immunosuppressive drug-naïve patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV).MethodsWe included 71 immunosuppressive drug-naïve patients newly diagnosed with AAV. Medical records were retrospectively reviewed and serum GPX-3 concentration was measured using serum samples collected and stored at diagnosis. The degree of vascular activity and extent of damage were assessed using the Birmingham vasculitis activity score (BVAS) and vasculitis damage index (VDI), respectively. Poor outcomes including all-cause mortality, end-stage kidney disease, and cerebrovascular and cardiovascular diseases were also investigated.ResultsThe median age of the study subjects was 63.0 years, 26 and 45 patients were males and females, respectively. The median GPX-3 concentration was measured as 82.8 ng/mL. Serum GPX-3 concentration at diagnosis was inversely correlated with BVAS (r = −0.280), VDI (r = −0.263), and C-reactive protein (r = −0.261) at diagnosis, whereas, it was positively correlated with haemoglobin (r = 0.255), and serum albumin (r = 0.240) at diagnosis, respectively. However, serum GPX-3 concentration at diagnosis was not significantly associated with poor outcomes during follow-up in patients with AAV.ConclusionIn this study, we demonstrated for the first time that serum GPX-3 concentration at diagnosis correlates with vasculitis activity and damage at diagnosis in patients with AAV, suggesting a possible role of serum GPX-3 as a complementary biomarker for assessing AAV activity in real clinical practice.